Current trends and prospects for the development of research in hydroabrasive cutting technology in mining and general engineering - A.М. Makhno (Технічна інженерія)
Hydroabrasive cutting technology (AWJ) is a practical material processing method that provides high accuracy, minimal thermal impact, and various industry applications. The article conducts a bibliometric analysis of waterjet cutting research using data from the scientometric databases Scopus and Web of Science (WoS). The primary attention is paid to analyzing the dynamics of publications, key research areas, and technological trends related to optimizing process parameters, numerical modeling, application in the mining industry, and environmental aspects of using technology. The R analytical package «bibliometrics» and VOSviewer software were used to conduct the study, which allowed us to visualize network connections between key terms, authors, research topics, and technology development trends. The analysis of the results revealed the main directions of development of waterjet cutting, including optimization of cutting parameters, improvement of the quality of machined surfaces, modeling of the processes of interaction of abrasive particles with the material, and automation of technological process control. A significant part of the scientific work is devoted to applying waterjet cutting in the mining industry, where this technology acts as an alternative to traditional drilling and blasting methods. There has also been increased research to reduce environmental impact, including water reuse and developing new abrasive materials. The study results allow us to systematize modern scientific trends and determine the prospects for further development of waterjet cutting technology, particularly in the context of industrial implementation and improvement of material processing methods.